Employability Skills Among Malaysian Polytechnics’ Architectural Graduates Involving Building Information Modelling (Bim) Intensive Training In Architecture Firm - Ishak, Nor Azida (2022)
This study aims to determine the levels of BIM-related skills among architecture graduates. This study also investigates which of the BIM skills can best predict the architecture graduates’ employability and the skills demanded by employers.